Image-Based Student Worksheet Development to Improve Student Learning Interest - Neviyani, Neviyani; Wijaya, Shendy Andrie; Mustofa, Amir (Classroom Action Research Journal (CARJO), 2019)
Student Worksheet (LKS) is a printed teaching material in the form of sheets of paper containing material, summaries, and instructions for implementing learning tasks that must be done by students. This study aims to determine the image-based student worksheets used can increase student interest in economic subjects in class X in Sulek High School. Development research uses the ADDIE development model (analysis, design, development, implementation, and evaluation). The sample in this study were 20th grade X students. The results of the development of the image-based worksheet for the analysis phase showed that students needed material that connected the material to everyday life. The design phase designs student worksheets by adding learning objectives and concept maps in the preamble, and adding images related to the material. The development phase consists of two stages, step 1 adding images according to the material and in step 2 adding sources to the images. The results of the LKS validation that have been developed increase from stage 1 to 3.5, stage 2, which is 3.9 stage 3, which is 4.7 with very good criteria. After the implementation phase shows the learning outcomes of students before using the worksheet reached a percentage of 25% after using the worksheets the students increased, namely in the first phase reaching a percentage of 75%, in the second stage 80% and in the third stage until reaching the highest number of subjects completing the value of 90%.KeywordsStudent Worksheet, Learning Outcomes